From stopover to wintering: Bewick`s Swans Cygnus columbianus bewickii in Schleswig-Holstein, northern Germany in winters 2016/2017 and 2017/2018 - Augst, Hans-Joachim; Hälterlein, Bernd; Fabricius, Katrin (Wildfowl, 2019)
In recent years, Schleswig-Holstein in northwest Germany has held up to a third of the Northwest European population of Bewick’s Swans Cygnus columbianus bewickii for several weeks, especially in March, as the birds staged in the region before continuing northeast to spring migratory sites in the Baltic Countries. Maximum numbers counted in Schleswig-Holstein during 2017 (5,591 birds) were recorded 10 days earlier (on 25 February) than the mean date of the peak count (7 March) recorded for nine previous winters for which the dates of the peak counts were known. Winter 2017/2018 started and ended with even higher numbers, including a new record count of 8,364 individuals on 24 February, perhaps reflecting warmer winter temperatures. Sightings of > 116 individual swans fitted with neck-collars or leg-rings gave detailed insight into their migration phenology. These ringed birds were recorded at sites south or southwest of the River Elbe especially in autumn before flying to Schleswig-Holstein, where they stayed for up to four months, albeit making short flights south or west during this period to cope with periods of snow. During these two winters, Bewick’s Swans appeared at several new sites where they had not previously been recorded by observers, and the survey areas therefore were enlarged. Three trends in the swans’ staging patterns are discussed: 1) an increase in numbers, 2) earlier arrival, and 3) longer staying by the swans in Schleswig-Holstein as a consequence of 1) and 2).